Effect of PVA on Mechanical Properties of Tapioca Starch Reinforced Coconut Fiber Biopolymer Composite - Md Yusof, Fauziah; Faridah Mat Taib, Che; ‘Aini Wahab, Nor; Leha Abdul Rahman, Noor; Kalam, Anizah; Salleh, Zuraidah (International Journal of Engineering and Technology, 2018)
The usage of polyvinyl alcohol (PVA) in polymer matrix has been explored for natural fiber composites to improve mechanical properties of the polymer. The PVA-modified tapioca starch was then used to produce coconut fiber composites. The study used 5 wt%, 10 wt% and 15 wt% of PVA in the tapioca starch. PVA-modified tapioca starch reinforced coconut fiber biopolymer composite was then proceeded with mechanical tests namely tensile test and impact test. All the specimens were tested in accordance to ASTM Standard; D3039/D3039M-08 and ASTM D256 for tensile properties and impact properties respectively. The results from the experiment showed that the tensile strength increased with increasing contents of PVA. PVA 15 wt% showed the highest tensile strength of 3.5 MPa. Another PVA contents of 5 wt% and 10 wt% showed tensile strength of 2.753 MPa and 3.064 MPa respectively. Apart from that, the result from impact test also showed that the impact energy increased with increasing content of PVA. PVA 15 wt% showed the highest impact energy of 1.054 J. Another PVA contents of 5 wt% and 10 wt% showed impact energy of 0.584 J and 0.872 J respectively.Â Â